2023
DOI: 10.15420/aer.2022.45
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Field Ablation for Atrial Fibrillation

Abstract: Catheter ablation is a widely used, effective and safe treatment for AF. Pulsed field ablation (PFA), as a novel energy source for cardiac ablation, has been shown to be tissue selective and is expected to decrease damage to non-cardiac tissue while providing high efficacy in pulmonary vein isolation. The FARAPULSE ablation system (Boston Scientific) follows the idea of single-shot ablation and is the first device approved for clinical use in Europe. Since its approval, multiple high-volume centres have perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A recent article reviewing clinical studies about PFA arrived at the same conclusion. [ 26 ] However, several limitations regarding the data need to be considered, and we likely underestimate the full extent of oesophageal involvement. Most patients (88%) this far have been treated with a single ablation system featuring a pentaspline catheter.…”
Section: Discussionmentioning
confidence: 99%
“…A recent article reviewing clinical studies about PFA arrived at the same conclusion. [ 26 ] However, several limitations regarding the data need to be considered, and we likely underestimate the full extent of oesophageal involvement. Most patients (88%) this far have been treated with a single ablation system featuring a pentaspline catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also proved durability of lesions with remapping at 90 days post initial procedure. 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies also proved durability of lesions with remapping at 90 days post initial procedure. 3,4 In a recent meta-analysis comparing PFA to other thermal energy sources, that is, RF and CA, 24 landmark studies were compared in terms of safety (perioprocedural complications) and efficacy (total procedure times/LA dwell times) and freedom for atrial arrhythmias at 1 year. It concluded that there were significantly lower complications with PFA compared to other thermal ablations, PFA group (2.05%; 95% CI 0.94-3.46) compared to the thermal ablation group (7.75%; 95% CI 5.40-10.47) (p 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed field ablation (PFA) is a novel, minimally thermal catheter ablation technology that creates lesions in myocardial tissue through irreversible electroporation [ 11 ]. It is currently limited to high-volume centers, but its adoption rate continues to grow for smaller centers.…”
Section: Introductionmentioning
confidence: 99%